(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Similar lap joints of pure copper C101 thin sheets were welded using pulsed laser welding. The effect of laser welding parameters on mechanical properties was investigated. The experimental results revealed that sound defect-free joints could be obtained from similar copper-copper joints where the fracture occurs away from the weld line. The present work proposes improved design control for three different pulse shapes; rectangular (normal), ramped-down and modulated which are used to weld six different copper samples to achieve the optimum tensile-shear strength of the joints. Results showed that modulated pulse shape has the optimum in the shear-tensile test. Ramped-down pulse shape had a less significant effect on the strength of the copper joint when compared with the rectangular pulse shape. The relationship between the input and output parameters was obtained by employing Minitab software, and the Matlab software was used in order to reach the optimum solution. The genetic algorithm showed that the optimum magnitude achieved for the shear strength was 77.9 MPa, and the optimum input parameters were pulse energy of 39J, the pulse width of 8.5, frequency of 10Hz and linear speed of 160mm/min.